Current diagnosis & treatment obstetrics & gynecology - DeCherney, Alan H. (McGraw-Hill Medical, 2013)
Provides coverage of more than 1,000 diseases and disorders. This title focuses on the medical and surgical management of obstetrics and gynecology. It also looks at the practical aspects of clinical diagnosis and patient management. It covers pathophysiology when relevant to diagnosis and treatment.